Pengaruh Model Project Based Learning dan Gaya Belajar terhadap Kemampuan Membuat Alat Permainan Edukatif untuk Anak Usia Dini pada Mahasiswa S-1 PG-PAUD Universitas PGRI Adi Buana Surabaya - Aulia Insani (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstract: The Influence of Project Based Learning Models and Learning Styles on the Ability to Make Educational Game Tools for Early Childhood in S-1 PG-PAUD Students of PGRI Adi Buana University Surabaya. The study aims to determine the influence of Project Based Learning Models and Learning Styles on the Ability to make Educational Game Tools for Early Childhood in S1 PG-PAUD Students of PGRI Adi Buana University Surabaya. This research uses a quantitative approach involving S1 PG-PAUD students class of 2015 classes A and B. data collected through learning style questionnaires, project assessment sheets and educational game tool assessment sheets. The respondents were 48 S1 PG-PAUD students class of 2015. There are only 2 free variables, namely project-based learning models and learning styles, while bound variables are the ability to make educational tools. The findings of this study show that the project-based learning model affects the ability to make educational game tools in early childhood while learning styles do not affect the ability to make educational game tools in students.